GERMAN’S BIOLOGICAL THEORIES IN CRIMINOLOGY - mapping the beginnings - Марина М. Симовић; Миомира П. Костић (Српска правна мисао)
In this paper, the author explores the early German criminology, pointing out that it was a result of interests stemming from the legalistic approach to crime. For this reason, the contribution of German criminologists to the development of criminology as an independent science is observed by examining the legalistic, anthropological, biological and sociological approaches to criminology. Each of these approaches is concurrently associated with a particular criminological orientation or a period of predominant influence of some criminological approach in explaining causality. The development of the German criminology at the time was reflected in the efforts of psychiatrists to expand their expertise into the field of criminal behaviour and to offer a medical solution to this problem. Tracing the historical development of the German criminology in the course of three different political regimes (including the German Empire, the Weimar Republic and the period of Nazism), the author of this article has an opportunity to assess the political impact on scientific research and its implications. Finally, the recent revival of the biological and genetic research into crimes makes this historical research into criminal biology (from Lombrose to Nazism) highly relevant. The historiography on crime and criminal justice in Germany is well-developed even though the German literature on these issues is considerably less extensive in volume than the respective literature in France and England. The knowledge of the social history of crime in Germany during the 19th and 20th century is still extremely limited. In the last decade of the 20th century, there were some significant developments in this process. In mapping the early development of criminology in Germany, Wetzell identifies the following historical periods. The first period is the beginning of the 19th century, marked by the learning of Lombroso on the inborn criminal offender as well as by the growing impact of the new criminal law reform in Germany. The second period involves the impact of the German reception of the Lombroso’s theory on establishing criminal psychology in Germany from 18801914. The third period reflects the learning of criminal sociology, i.e. accepting the idea on the impact of social conditions on the development of crime. The next period covers the predominant position of the biological research in criminology at the time of the Weimar Republic. Finally, the last period in the development of the earlier German criminology is the period under the Nazi regime (including the sterilization of criminals as well as the Nazi policy of sterilizations of some ethnic groups).